2008
DOI: 10.1128/jb.00990-07
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Sensor Kinases in the Stress Tolerance Response ofStreptococcus mutans

Abstract: The gram-positive bacterium Streptococcus mutans is the primary causative agent in the formation of dental caries in humans. The ability of S. mutans to adapt and to thrive in the hostile environment of the oral cavity suggests that this cariogenic pathogen is capable of sensing and responding to different environmental stimuli. This prompted us to investigate the role of two-component signal transduction systems (TCS), particularly the sensor kinases, in response to environmental stresses. Analysis of the ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(127 citation statements)
references
References 68 publications
5
115
0
7
Order By: Relevance
“…These results suggest that inactivation of each of these systems results in a mutant that has a reduced growth rate at acidic pH. Recent studies have shown that several TCS have been involved in acid resistance in S. mutans (Ahn et al, 2006;Biswas et al, 2008;Li et al, 2002;Lévesque et al, 2007;Kawada-Matsuo et al, 2009). Some of the TCS identified to be involved in acid tolerance in these studies appear to be different from those in our study, probably owing to the differences in the strains, mutant construction, growth conditions and assay methods.…”
Section: Effect Of Inactivation Of the Histidine Kinases (Hk) On Atrmentioning
confidence: 76%
See 1 more Smart Citation
“…These results suggest that inactivation of each of these systems results in a mutant that has a reduced growth rate at acidic pH. Recent studies have shown that several TCS have been involved in acid resistance in S. mutans (Ahn et al, 2006;Biswas et al, 2008;Li et al, 2002;Lévesque et al, 2007;Kawada-Matsuo et al, 2009). Some of the TCS identified to be involved in acid tolerance in these studies appear to be different from those in our study, probably owing to the differences in the strains, mutant construction, growth conditions and assay methods.…”
Section: Effect Of Inactivation Of the Histidine Kinases (Hk) On Atrmentioning
confidence: 76%
“…Using real-time qRT-PCR, we confirmed the same trend in the expression of these genes, including the genes encoding their cognate response regulators, in response to acidic pH (Table 2). In the S. mutans genome, there are 14 TCSs, and at least one orphan response regulator has been identified (Ajdic et al, 2002;Biswas et al, 2008;Idone et al, 2003). Some of these systems, such as LiaSR (formerly HK/ RR11), CiaHR, ComDE and CovR, have been found to play a role in acid resistance and considered as a major attribute to the virulence of S. mutans (Ahn et al, 2006;Idone et al, 2003;Li et al, 2001bLi et al, , 2002Lévesque et al, 2007;Kawada-Matsuo et al, 2009).…”
Section: Upregulated Genesmentioning
confidence: 99%
“…Gryllos et al (21,22) reported that the presence of Mg 2ϩ in the growth medium stimulated the activity of CovR/S, specifically acting as a stimulant for CovS. In the absence of CovS, it is possible that Mg 2ϩ activates one of the previously identified TCS of S. mutans (5), which subsequently leads to the transcription of covR or the activation of CovR in S. mutans. However, the increase in the expression of covR under in vitro conditions was observed using concentrations of Mg 2ϩ that are significantly higher than physiological conditions; the concentration of Mg 2ϩ in saliva is 0.22 mM, while the concentration of Mg 2ϩ in blood is approximately 1 mM (22,47).…”
Section: Discussionmentioning
confidence: 99%
“…S. mutans adheres to the tooth surface and forms dental plaque, a classic biofilm. The pH of the oral cavity is predominantly acidic; within the dental plaque, S. mutans induces an acid-tolerance response that favors its survival under low pH conditions (4).…”
Section: Introductionmentioning
confidence: 99%